Measurements of Nonlinear Coefficient in OS2 Optical Fiber - Porins, J.; Ivanovs, G.; Supe, A. (Elektronika ir Elektrotechnika, 2010)
The nonlinear coefficient of the various optical fibers types has been experimentally and with OptSim 5.0 simulation software studied. With the help of CW SPM, P-SPM and XPM measuring methods the following parameters have been determined experimentally: nonlinear coefficient n2/Aeff and nonlinear refractive index n2; accordingly, n2/Aeff is calculated to be in the range 1.24·10-12 - 5.26·10-10 1/W, whereas n2 − in the range 3.38·10-23 - 4.21·10-20 m2/W. As seen from results the OS2 fibers have smaller variation of nonlinear coefficient values at different measurement methods in contrast to SSMF and DSF fibers. OS2 fiber n2 value stability are in the limits from 2.88·10-20 m2/W in case of P-SMP method to 2.9·10-21 m2/W in case of CW SMP method.